Effect of Aging on the Trunk and Lower Limb Kinematics during Gait on a Compliant Surface in Healthy Individuals - Keita Honda; Yusuke Sekiguchi; Shin-Ichi Izumi (Biomechanics, 2023)
Older adults have a smaller effective living space and reduced physical activity. Although walking ability in various living spaces is necessary to maintain a healthy life and a high level of physical activity, it is unclear how older adults adapt to compliant surfaces when walking. The purpose of this study was to determine the differences in the trunk and lower limb kinematics while walking on a level versus compliant surface, and the effect of aging on these kinematic changes. Twenty-two healthy individuals (aged from 20–80 years) were asked to walk along a 7-m walkway at a comfortable speed on a level and compliant surface. Gait kinematics were measured using a three-dimensional camera-based motion analysis system. We found that knee and hip flexion and ankle plantarflexion angles in the early stance phase and thoracic flexion angle throughout the gait cycle were significantly increased when walking on a compliant surface versus a level surface. The change in the thoracic flexion angle, ankle plantarflexion angle, and cadence between level and compliant surfaces was significantly correlated with age. Therefore, older adults use increased thoracic flexion and ankle plantarflexion angles along with a higher cadence to navigate compliant surfaces.